THE WIN-WIN STRATEGY WITH COOPETENCE IN THE HOTEL / TOURISM SECTOR IN THE RIOBAMBA CANTON - Cuzquillo Cusquillo, Edgar; Guillin Nuñez, Milton (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
There are circumstances in the business environment in which you must face in a more organized way, that is, in teams made up of a group of competitors from the same industry or complementary industries, for their growth and development, with the objective of achieving growth and market development. It must be clear that currently the market is alive, versatile and very dynamic, organizations seek to win based on their own interests, but it must be borne in mind that in negotiation this could bring us conflicts and thereby breakdown of relationships, the most coherent is look for the way that both parties benefit, that both win. That is why it is essential to implement the Win-Win strategy with Coopetencia, seeking cooperation and mutual benefit of the parties.